Electrical stimulation mapping of the pulmonary artery in swine: impact on pulmonary artery denervation procedure for pulmonary hypertension. (25th November 2020) - Condori Leandro, H.I; Goncharova, N; Vakhrushev, A; Korobchenko, L; Andreeva, E; Murashova, L; Voronin, S; Mitrofanova, L; Moiseeva, O; Lebedev, D; Mikhaylov, E
Abstract: Introduction: Pulmonary artery denervation (PAD) has been recently shown to decrease pulmonary artery (PA) pressure. However, there is a lack of data related to target sites for ablation. Purpose: To determine the optimal PA ablation sites based on response to high-frequency stimulation mapping and anatomical areas where radiofrequency ablation (RFA) should be avoided due to the risk of severe collateral damage. Methods: A total of 17 Landrace swines were included into the study. PA angiography, hemodynamic measurements by right heart-sided catheterization and electrophysiological mapping (EM) using low (cycle length 330 ms) and high-frequency (33Hz) stimulation (HFS). Stimulation was performed at PA bifurcation and proximal parts of the main PA branches with a 5-mm distance between points; catheter manipulation was performed under fluoroscopic guidance in multiple projections. Points with evoked reactions were tagged on a 3-dimentional PA model in each case. In order to confirm reproducibility of reactions, HFS was performed at least twice at each point with a response. PA models obtained from all animals were combined in one for the final analysis. RFA using an open-irrigated catheter (40 Watts; 40 s; irrigation 30 ml/min) were performed at sites with evoked reactions. Repeated HFS was performed at ablation sites. After the procedure all animals were euthanized and underwent an autopsy study. Results: Low-frequency stimulation (LFS) allowed to define areas of ventricular capture (VC) where HFS was avoided due to ventricular fibrillation induction risk. During HFS the following evoked responses were documented: sinus bradycardia, sinus rhythm (SR) acceleration, phrenic nerve capture (PNC), and laryngeal recurrent nerve capture. HFS captured left and right phrenic nerves in all animals at PA trunk, and its course was tagged (Figure 1). Laryngeal recurrent nerve capture was found in 4 (23%) of animals. Atrial capture was found in all cases while LFS at the anterior aspects of both PAs even at low output, and this precluded evaluation of neural autonomic reactions in these areas. Evoked bradycardia and SR acceleration were both found during HFS in 10 (59%) of cases each. Following RFA application evoked reactions were non-reproducible in all cases. RFA was applied in areas where no PNC or VC points were observed. An autopsy study confirmed the presence of RF-induced lesions of the PA wall. Conclusions: There are two important findings of our study. First, stimulation-guided PA mapping is feasible and reveals several specific responses to HFS. Ablation at points with responses leads to non-reproducibility of the evoked reactions, confirming that transcatheter RFA may be an adequate approach for PA denervation. Second, previously proposed circular PA ablation might be associated with phrenic and laryngeal recurrent nerve damage. Stimulation-guided PA denervation can be proposed as a safer procedure, and should be evaluated in clinical settings. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Russian Foundation for Basic Research